2019
DOI: 10.47895/amp.v53i1.235
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Thiel Soft-embalmed and Formalin Preserved Cadavers for Anatomy Dissection

Abstract: Background and Objective. Cadavers are the main teaching and learning tools utilized by faculty and students of Gross Anatomy. The conventional procedure of using formalin to preserve cadavers has its limited benefit due to its obnoxious odor, darkened color, indistinguishable small structures, rigid joints, with friable organs and tissues. Using the Thiel Method, cadavers are known to have: life-like presentation, a high degree of suppleness, natural mobilization of various body parts with tolerable odor, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…6 The colour of the tissues has a significant impact on their ease of use and drawing similarity to live tissue. Dissection quality and students' understanding of anatomy were found to be significantly enhanced when tissues were preserved in a manner analogous to that of fresh specimens, as reported by Villacorta et al 11 Tissue colour plays a significant role in the realism and lifelike appearance of cadavers, which can affect students' comfort levels and engagement during dissection and learning activities. 5,12 Comparing the tissue colour of TECs and FECs can provide insights into the potential benefits and limitations of using Thiel embalming for anatomical education.…”
Section: Discussionsupporting
confidence: 59%
“…6 The colour of the tissues has a significant impact on their ease of use and drawing similarity to live tissue. Dissection quality and students' understanding of anatomy were found to be significantly enhanced when tissues were preserved in a manner analogous to that of fresh specimens, as reported by Villacorta et al 11 Tissue colour plays a significant role in the realism and lifelike appearance of cadavers, which can affect students' comfort levels and engagement during dissection and learning activities. 5,12 Comparing the tissue colour of TECs and FECs can provide insights into the potential benefits and limitations of using Thiel embalming for anatomical education.…”
Section: Discussionsupporting
confidence: 59%
“…al surmised that Thiel soft-embalmed cadavers were more life-like and "had the potential for research and practicing skills, such as endoscopy, laryngoscopy, and intubation". 17 Another local study by Grullo et al used soft-embalmed cadavers for surgical simulation of endoscopic sinus surgery, with the conclusion that the operation could be practiced with high fidelity and still present with the same technical difficulties. 18 Other studies have utilized Thiel cadavers to train in fiberoptic tracheal intubation, 19 facemask ventilation, direct laryngoscopy, and tracheal intubation, 20 but none for upright procedures.…”
Section: Thiel Cadaver Chairmentioning
confidence: 99%
“…5,13 It is reported that the internal organs, blood vessels, nerves and muscles become rough, stodgy and dull in formalin-embalmed cadavers. 14 Liver resection requires extensive mobilization of liver and such a wide range of manipulation may not be possible in formalin-embalmed cadavers, making them unsuitable for surgical skill training. Formalin cadavers have a characteristic acrid smell and burning sensation in the eyes, which makes training in formalin cadavers for prolonged periods difficult.…”
Section: Journal Of Clinical and Experimental Hepatologymentioning
confidence: 99%
“…Formalin cadavers have a characteristic acrid smell and burning sensation in the eyes, which makes training in formalin cadavers for prolonged periods difficult. 14 In contrast to formalin-embalmed cadavers, Thiels-embalmed cadavers are more suitable for use in surgical skill training. 15 Thiels-embalmed cadavers offer lifelike colour, consistency and fidelity to the tissues and offer a good range of joint movement.…”
Section: Journal Of Clinical and Experimental Hepatologymentioning
confidence: 99%